2001
DOI: 10.1080/01468030151072976
|View full text |Cite
|
Sign up to set email alerts
|

Strip-Loaded Sol-Gel Waveguides: Design and Fabrication

Abstract: Sol-gel is one of the most attractive techniques for production of silica-on-silicon integrated optical devices. In fact, it combines low cost with flexibility and ease of doping; thus, nonlinear and active compounds can be effectively included in the silica matrix. Here, the feasibility of applying the sol-gel technique to the realization of an erbium-doped optical amplifier is reported on, operating in the third telecommunication window. In particular, the development of an optimum strategy for the design an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Several techniques have been investigated for the productions of silica based integrated planar waveguides. In particular sol-gel is one of the most promising techniques because of its relatively low cost and high versatility [2,3]. Among the several silica-based glasses it was demonstrated that the SiO 2 -HfO 2 binary system presents valuable prospects for successful photonic applications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques have been investigated for the productions of silica based integrated planar waveguides. In particular sol-gel is one of the most promising techniques because of its relatively low cost and high versatility [2,3]. Among the several silica-based glasses it was demonstrated that the SiO 2 -HfO 2 binary system presents valuable prospects for successful photonic applications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the sol-gel process has emerged as an effective route for the fabrication of SiO 2 -based planar waveguides with valuable prospects for EDWAs fabrication [7][8][9][10]. In previous papers we presented some results about a set of 70SiO 2 -30HfO 2 planar waveguides, doped with different erbium concentration ranging between 0.01 and 4 mol%, prepared by the sol-gel technique with dip-coating processing.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Among the silica-based systems, binary SiO 2 -TiO 2 has been widely used to produce Er-activated planar waveguides by sol-gel route. 1,2,8,9 However, in the silica-titania system, there is a tendency for separation between SiO 2 -rich and TiO 2 -rich phases. Undesirable phase precipitation can take place as a consequence of the thermal treatment, necessary to achieve full densification of the film, or during the reflow process.…”
mentioning
confidence: 99%
“…[1][2][3] In particular, SiO 2 based planar waveguides produced by sol-gel route, could be promising materials for Erdoped waveguide amplifiers ͑EDWA͒ to be used in metropolitan area networks. [1][2][3][4][5] The key requirements for developing EDWAs by the sol-gel route are: ͑i͒ refractive index and thickness of the film have to be tailored, in order to satisfy both single-mode condition at 1.5 m and efficient coupling to fibers; ͑ii͒ the structural and optical homogeneity have to be optimized, in order to reduce losses and rare-earth clustering; 1,5 and ͑iii͒ the OH groups must be effectively removed, because the 4 I 13/2 luminescence of OH Ϫ -coordinated Er 3ϩ ions is completely quenched by two phonon-OH mechanism. 6,7 Among the silica-based systems, binary SiO 2 -TiO 2 has been widely used to produce Er-activated planar waveguides by sol-gel route.…”
mentioning
confidence: 99%